International Education in WA: An Update on Enrolment Trends and Economic Contribution, Briefing Note for StudyPerth - Duncan, Alan; Phillimore, John; Kiely, Daniel (2018)
This note provides a detailed update on international student enrolment trends in WA to May 2018 and the economic contribution of the sector to the WA economy for 2017. An update on Government policy settings towards international education across Australia, including budgeted spend, is also provided.